Community Priority setting for Fetal Alcohol Spectrum Disorder Research in Australia - Finlay-Jones, Amy; Symons, Martyn; Tsang, Tracey W; Mullan, Narelle; Jones, Heather; McKenzie, Anne; Reibel, Tracy; Cannon, Lisa; Birda, Bridgette; Reynolds, Neil; Sargent, Paula; Gailes, Helen; et al. (International Journal of Population Data Science, 2020)
Introduction Fetal Alcohol Spectrum Disorder (FASD) is a neurodevelopmental disorder caused by prenatal alcohol exposure (PAE). FASD research is a rapidly growing field that crosses multiple disciplines. To ensure research is relevant and meaningful for people living with FASD, their families, and the broader public there is a need to engage community members in setting priorities for research. Objectives Our primary objective was to formally identify the views of people living with FASD, their par- ents/caregivers, service providers, and the general community on the research priorities for FASD and alcohol use in pregnancy in Australia. Our secondary objective was to provide an overview of current research in the highest priority areas identified. Methods The approach for this study involved two community surveys and a consensus workshop, followed by a rapid literature review. Survey responses (n = 146) were collected and grouped using qualitative thematic analysis. The themes identified were then ranked in a second survey (n = 45). The 22 highest ranked themes were considered in a workshop with 21 community members, and consensus on the top ten priority areas was sought. The priority areas were grouped into conceptually similar topics and rapid literature reviews were undertaken on each. Results A diverse range of priorities was identified within key areas of prevention, diagnosis, and therapy. On request from participants, separate priority lists were developed by Aboriginal and non-Aboriginal participants. Conclusions There is need for a national network of researchers to take forward the research commenced by the Centre of Research Excellence, FASD Research Australia, in addressing community priorities.